A photoactivatable Ru (II) complex bearing 2, 9-diphenyl-1, 10-phenanthroline: A potent chemotherapeutic drug inducing apoptosis in triple negative human breast adenocarcinoma cells. (25th February 2021) - Mansour, Najwa; Bodman-Smith, Kikki; Khnayzer, Rony S.; Daher, Costantine F.
Abstract: The photoactivatable Ru (II) complex 1 [Ru(bipy)2(dpphen)]Cl2 (where bipy = 2, 2′-bipyridine and dpphen = 2, 9-diphenyl-1, 10-phenanthroline) has been shown to possess promising anticancer activity against triple negative adenocarcinoma MDA-MB-231 cells. The present study aims to elucidate the plausible mechanism of action of the photoactivatable complex 1 against MDA-MB-231 cells. Upon photoactivation, complex 1 exhibited time-dependent cytotoxic activity with a phototoxicity index (P Index) of >100 after 72 h. A significant increase in cell rounding and detachment, loss of membrane integrity, ROS accumulation and DNA damage was observed. Flow cytometry and a fluorescent apoptosis/necrosis assay showed an induction of cell apoptosis. Western blot analysis revealed the induction of intrinsic and extrinsic pathways and inhibition of the MAPK and PI3K pathways. The photoproduct of complex 1 showed similar effects on key apoptotic protein expression confirming that it is behind the observed cell death. In conclusion, the present study revealed that complex 1 is a potent multi-mechanistic photoactivatable chemotherapeutic drug that may serve as a potential lead molecule for targeted cancer chemotherapy. Graphical abstract: Image 1 Highlights: A photoactivatable polypyridyl ruthenium(II) complex with reduced side-effects and enhanced efficacy against cancer cells. A photoactivatable polypyridyl ruthenium(II) induces both intrinsic and extrinsic apoptosis in TNBC cells. A photoactivatable polypyridyl ruthenium(II) induces cancer cell rounding/detachment and loss of membrane integrity. A photoactivatable polypyridyl ruthenium(II) complex induces cellular ROS accumulation and DNA damage in cancer cells. A photoactivatable polypyridyl ruthenium(II) complex induces cancer cell death through inhibition of MAPK and PI3K pathways.